The two ways of FDI R&D spillovers: evidence from the French manufacturing industry. Issue 25 (28th May 2017) - Ben Hassine, H.; Boudier, F.; Mathieu, C.
ABSTRACT: Using French firm-level panel data, this study investigates R&D spillovers from inward foreign direct investment (FDI) with respect to both horizontal and vertical linkages (backward and forward). Using a Crepon, Duguet and Mairesse (CDM) model, we estimate an R&D-augmented Cobb–Douglas production function to assess the impact of R&D spillovers on firm performance. The results emphasize that international spillovers (from foreign affiliates to local firms) have a greater effect on firm performance than reverse spillovers (from local firms to foreign affiliates) and are more likely to be backward than forward. Moreover, the effect of backward spillovers depends on a firm's absorptive capacity and is amplified in the case of outsourcing relationships.